Hydrogel Activity Test from Kirinyu Leaf Ethanol Extract (Chromolaenaodorata (L.) R. King & H. Rob) and Combination of Kirinyu Leaf Ethanol Extract with Collagen As A Healing Wound Excision. - S, Thursina C; R, Julia; S, Sumaiyah (Asian Journal of Pharmaceutical Research and Development, 2020)
Objective: the purpose of this study was to determine the activity of the kirinyu leaf ethanol extract hydrogel preparation and the combination of the kirinyu leaf ethanol extract with collagen as a healing wound excision. Method: This research is experimental, where the ethanol extracts of Kirinyu leaves and collagen are formulated in the form of hydrogel preparations and tested on the healing of excision wounds in rats. Testing wound healing activities were divided into 6 groups. The Group 1 (negative control) were given hydrogel base without Kirinyu leaf ethanol extract in combination with collagen, group 2 (positive control) were given Octenilin®gel, groups 3 and 4, were given hydrogel of Kirinyu leaf ethanol extract while groups 5 and 6 were given hydrogel extract of kirinyu leaves combined with collagen. Result: The results of percent reduction in wound diameter showed that groups 3 and 4 gave significant differences compared to group 1 which began to be seen on the 10th day (p <0.05). While groups 5 and 6 gave significant differences that began to be seen on the 8th day (p <0.05). Conclusion:Hydrogel preparation in group 6 has the most potential in healing excision wounds.